2020
DOI: 10.1071/sr19373
|View full text |Cite
|
Sign up to set email alerts
|

Soil biochemical activities after the application of pyroligneous acid to soil

Abstract: Pyroligneous acid (PA) is produced during the combustion of woody biomass and is a complex aqueous fraction resulting from the thermochemical rupture of the components of vegetable biomass. We evaluated the effect of PA on the soil microbial community and activity in order to assess the applicability of this acid in soil and to gather further information on the mechanisms of its toxicity or stimulation. Five concentrations of PA solution (0, 0.5, 1, 2 and 5%) were selected to monitor the biochemical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 38 publications
3
19
0
1
Order By: Relevance
“…Among PAHs, only acenaphthylene and phenanthrene reached 0.09 ng L –1 , well below the most restrictive legislative limits. In this study, the WD was applied at a 1% dilution in order not to interfere with the soil enzyme activities, according to previous investigation by the same research group (Cardelli et al., 2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among PAHs, only acenaphthylene and phenanthrene reached 0.09 ng L –1 , well below the most restrictive legislative limits. In this study, the WD was applied at a 1% dilution in order not to interfere with the soil enzyme activities, according to previous investigation by the same research group (Cardelli et al., 2020).…”
Section: Methodsmentioning
confidence: 99%
“…It has also been reported that the application of WD can promote plant growth (Simma et al., 2017), increasing the content of mineral and nutritional elements in the soil (Polthanee et al., 2014). Furthermore, the acidic nature of WD can regulate soil pH (Lashari et al., 2015), improve nutrient availability (Lashari et al., 2013), inhibit ammonium loss (Grewal et al., 2018), mitigate N 2 O and CH 4 emissions (Sun et al., 2018), and influence the soil microbial community (Cardelli et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…50% increase in chlorophyll content and growth of lettuce (Lactuca sativa L.) [4]. Recently, a pre-biotic activity of WD has been reported also for soil biota [5]. Therefore, WD can be regarded as a valid candidate for the replacement of several chemical products routinely used worldwide in the agri-food industry [1,6].…”
Section: Introductionmentioning
confidence: 99%
“…[110][111][112][113] A PA concentration of 10% significantly enhanced plant growth, fruit weight, fruit diameter and sweetness of fruits. 111 Siriwardena et al 113 PA applied to the soil improves its physical, chemical, and biological properties, providing an increase in beneficial microorganisms [116][117][118][119] and facilitating the absorption of nutrients from the soil solution by plants. 120 Koç et al 117 reported that in general the dose of PA of 3.0% ml will promoted a positive effect on the number and activity of biological factors in soil.…”
Section: Application Of Pamentioning
confidence: 99%